2020
DOI: 10.1177/1069072720941269
|View full text |Cite
|
Sign up to set email alerts
|

Parenting, Major Choice Motivation, and Academic Major Satisfaction Among Filipino College Students: A Self-Determination Theory Perspective

Abstract: Guided by Self-Determination Theory (SDT), this study examined the relationships among parenting (autonomy-supportive and controlling), major choice motivations (autonomous and controlled), and academic major satisfaction with a sample of 525 Filipino college students. Consistent with the hypotheses, the results of structural equation modeling indicated that perceived autonomy-supportive and controlling parenting were positively associated with autonomous and controlled major choice motivations, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
0
6
0
1
Order By: Relevance
“…Nerona (2020) [97] showed in a recent study, those parents that have more education years take shared decisions concerning their kids' education; maternal support is notably associated with the motivation to fulfill adolescents' academic goals. Previous evidence indicated the existence of an association between the mothers' education level and academic achievement.…”
Section: Hypothesis Discussionmentioning
confidence: 99%
“…Nerona (2020) [97] showed in a recent study, those parents that have more education years take shared decisions concerning their kids' education; maternal support is notably associated with the motivation to fulfill adolescents' academic goals. Previous evidence indicated the existence of an association between the mothers' education level and academic achievement.…”
Section: Hypothesis Discussionmentioning
confidence: 99%
“…Fourth, while many studies from collectivistic societies have examined the utility of SDT’s tenets and central variables (e.g., autonomy support, self-determined motivation, well-being; Belle et al, 2022; Chang et al, 2016), research from these contexts applying SDT to career choice and career development remains relatively scarce (Lin et al, 2015; Nerona, 2021). Thus, testing the mediating role of self-concordant major choice helps enrich the contextual applicability of SDT.…”
Section: Discussionmentioning
confidence: 99%
“…Second, by using a Chinese sample, we further enrich the applicability of SDT and the concept of self-concordance in the collectivist culture. SDT is fertile for explicating the formation and influence of self-determination, even for those from non-Western cultures (Nerona, 2021). SDT-based studies from China have shown that psychological need satisfaction is essential for self-concordant motivation, which promotes optimal human development and well-being (Belle et al, 2022; Chang et al, 2016; Xu et al, 2021), supporting the application of SDT and self-concordance to collectivist contexts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on SDT, students’ perceptions of voluntary autonomy, competence, and relatedness in academic majors fully mediate the relations between perceived faculty and peer support and major satisfaction ( Schenkenfelder et al, 2020 , 265–273). In addition, autonomous major choice motivation mediates the relation between autonomy-supportive parenting and academic major satisfaction, and controlled major choice motivation mediates the association between controlling parenting and academic major satisfaction ( Nerona, 2021 , 205–220).…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%